An environment Kuznets curve for ecological footprint: Evidence from GCC countries - Mohd Arshad Ansari; Muhammad Rais Ahmad; Safeera Siddique; Kashif Mansoor (Carbon Management, 2020)
Using country’s ecological footprint, the present empirical study aims to analyze the influence of the economic growth, energy consumption, and globalization on ecological footprint in the Environmental Kuznets curve (EKC) model for the Gulf Cooperation Council (GCC) countries; namely Bahrain, Oman, Qatar, Saudi Arabia and the UAE covering the period 1991-2017. By employing panel econometric approaches that considered issues of heterogeneity and cross sectional dependence, we find that all variables are first-difference stationary by using the cross-sectional augmented IPS (CIPS) and the cross-sectional augmented Dickey-Fuller (CADF) unit root tests. There exists a long-run relationship among examined variables tested by using the Westerlund cointegration tests statistics. By employing the dynamic ordinary least square (DOLS), and the fully modified ordinary least square (FMOLS), we also find that increase in the consumption of energy and globalization increases the ecological footprint, and the EKC hypothesis is not supported for the GCC countries. From the outcome of this empirical work a number of policy implications have been discussed in the study.